Loading and draining of periodically operated trickle bed reactor - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT Periodic interruption of liquid flow in cocurrent trickle beds appears to be an attractive mode of operation. For modelling these intermittent flow reactors, loading and draining times must be known. Experiments were undertaken using beds of activated carbon with water and air as the fluid phases. Loading time was taken as water brealarough. The gas flow was continuous while the time between the end of drainage and the start of filling was varied to simulate different periods. Drainage experiments followed the liquid flow leaving the bed as a function of time. Liquid hold ups were determined after the filling and draining measurements. Variable considered were particle size, gas and liquid velocities. Loading closely follows the plug flow model